2020
DOI: 10.1109/tvcg.2018.2869729
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Focal Distance, Age, and Brightness on Near-Field Augmented Reality Depth Matching

Abstract: Many augmented reality (AR) applications operate within near-field reaching distances, and require matching the depth of a virtual object with a real object. The accuracy of this matching was measured in three experiments, which examined the effect of focal distance, age, and brightness, within distances of 33.3 to 50~cm, using a custom-built AR haploscope. Experiment~I examined the effect of focal demand, at the levels of collimated (infinite focal distance), consistent with other depth cues, and at the midpo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 46 publications
3
43
0
2
Order By: Relevance
“…An explanation for this phenomenon is that collimating optics cause eyes' vergence angle to rotate outward by a constant angular amount. Singh et al's experiment confirmed these results and showed that the bias of vergence angle bias is constant within distances of 33.3 to 50 cm when the subjects match virtual targets in AR. They also found that presenting AR objects at the AR display's focal distance results in more accurate depth matches.…”
Section: Related Workmentioning
confidence: 78%
“…An explanation for this phenomenon is that collimating optics cause eyes' vergence angle to rotate outward by a constant angular amount. Singh et al's experiment confirmed these results and showed that the bias of vergence angle bias is constant within distances of 33.3 to 50 cm when the subjects match virtual targets in AR. They also found that presenting AR objects at the AR display's focal distance results in more accurate depth matches.…”
Section: Related Workmentioning
confidence: 78%
“…Another possible explanation for this phenomenon could rely on luminance. Indeed, luminance has been reported as being a strong factor for depth estimation for real objects [1,4,7] or more recently in AR [25]. More saturated and brighter objects tend to be perceived as nearer than less saturated and bright objects.…”
Section: Discussionmentioning
confidence: 99%
“…Within near-field reaching distances, Singh et al [43] investigated the effects of focal distance, age and brightness when matching the depth between a real and virtual object using an haploscope within distances between 33.5-50 cm in a depth-matching task [46].…”
Section: Perceptual Issues In Ost Hmdsmentioning
confidence: 99%